Prediction of salmon (Salmo salar) quality during refrigeration storage based on dielectric properties - He, Jialing; Li, Feng; Jiao, Yang (International Journal of Agricultural and Biological Engineering, 2021)
Dielectric properties are validated to be correlated with the changes of food quality during 4°C storage, thus it could be used as predictive indicators for the quality parameters of salmon (Salmo salar) during cold storage. An open-ended coaxial detection method was used to determine the dielectric properties (dielectric constant ε’ and dielectric loss ε") of salmon at the frequency range of 20-2500 MHz, and to explore the relationship between dielectric properties and volatile base nitrogen (TVB-N), thiobarbituric acid reactants (TBARS), total viable counts (TVC), pH and K-value in salmon fillets during storage for 7 d. Results showed that the TVB-N, TBARS, TVC and K-value of salmon increased linearly with the increase of storage time, and the pH decreased firstly and increased subsequently. Also, the dielectric properties (ε’ and ε") decreased with the increase of frequency, and increased with the increase of storage time. During 7 d storage, ε" increased the most at the frequency of 27.12 and 40.68 MHz, while at the frequency of 915 MHz and 2450 MHz, the increase of ε" was smaller. Results analyzed by Pearson correlation analysis showed that significant correlation (p<0.01) was found between ε" and TVB-N and TBARS at the frequency of 27.12, 40.68, 100, 300 and 915 MHz. The results of the partial least square (PLS) model showed that all the determination coefficients (R2pred) were over 0.900. Especially for TBARS, the R2pred of PLS-ε’ and PLS-ε" were 0.913 and 0.920, respectively, and the root mean square error of prediction (RMSEP) were 0.041 and 0.039, respectively. However, the highest R2pred for PLS-ε’ and PLS-ε" both occurred in TVB-N. Also, the predicted values against measured values of TVB-N, TBARS and TVC of salmon presented a good linear relationship. The linear coefficient R2 of TVB-N, TBARS and TVC for PLS-ε’ were 0.937, 0.910 and 0.917 respectively, and 0.942, 0.917 and 0.933 respectively for PLS-ε". The results demonstrated the dielectric properties combined with PLS analysis can be used as a rapid and non-destructive method to predict quality parameters of salmon during 4°C storage and could be further applied to other aquatic products. Keywords: seafood, physiochemical quality, dielectric properties, PLS regression, non-destructive food analysis, Salmon DOI: 10.25165/j.ijabe.20211404.6281 Citation: He J L, Li F, Jiao Y. Prediction of salmon (Salmo salar) quality during refrigeration storage based on dielectric properties. Int J Agric & Biol Eng, 2021; 14(4): 262–269.